Penilaian Kebutuhan Petani atas Prasarana Usaha Tani pada Hamparan Sawah Beririgasi - Mohamad Yanuar Jawardi Purwanto (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
The reliable paddy field infrastructure required to boost agricultural production needs. These requirements should be planned as an opportunity increasing farmer’s income to alleviate poverty and to achieve food security in national level. Farm infrastructure covers farm road, irrigation, and drainage in the existing irrigated paddy field. The existing farm infrastructure only have limited farm road, unstable irrigation canal, and without proper drainage system. For the sustainability of irrigated existence of paddy field infrastructure the needs and level of technology needed to consider the farmers opinion, so they can improve the existing agricultural infrastructure. The purpose of this activity are to reviewing the farmers perceptions about the needs of farmers irrigation infrastructure on paddy field with the way do focus group discussion (FGD). By conducting FGD in the irrigated paddy fields, farmers in Cianjur agree to adopt facilities of farm infrastructure. The results showed that farmers need farm roads, irrigation pipes, and the arrangement of paddy fields to be more organized and easier to do activity of farming. To infrastructure development of farming, the farmers agreed to build farm roads by utilizing the existing chanel kuarter and changing the ground channels of quarter with irrigation pipes.